단기간의 크레아틴 섭취가 태권도 선수의 발차기 횟수, 혈장요소 및 무산소성 파워에 미치는 영향 - 이호성(Ho-Song Lee) (한국콘텐츠학회 논문지, 6(4), 2006)
The main purpose of the present study was to find the effect of short term creatine loading on repeated bouts of kicking, plasma creatine phosphokinase and anaerobic power in male taekwondo player from high school. Eighteen male were randomly assigned to two groups. They were tested before and after 6 days of placebo($4{×}5$ glucose d-1, N=9) or Creatine monohydrate loading(consume 0.3g kg-1, N=9). Only creatine loading group were significantly increased of repeated bouts of kicking, plasma creatine phosphokinase and anaerobic power These results suggest that short creatine loading was effective diet protocol in taekwondo player from male high school. 본 연구는 Cr 투여가 태권도 선수들에게 발차기 횟수, 혈장요소 및 무산소성 파워에 어떠한 영향을 미치는지를 규명하기 위하여 수행되었다. 이를 위하여 남자 고등학교 태권도 선수를 대상으로 위약집단(n=9명), Cr 투여집단(n=9명)으로 구분하여 Cr을 투여한 결과 Cr 투여집단에서만 발차기 횟수, 혈장효소, 무산소성 파워(평균파워, 최대파워)에서 각각 유의하게 증가하였다. 이러한 결과들은 Cr 투여가 태권도 선수들에게 있어서 효과적인 영양 보조물 방법이고, 단기간의 Cr 투여로도 발차기 횟수의 향상에 긍정적인 영향을 미칠 수 있음을 확인할 수 있었다.